Computer tomography urography assisted real-time ultrasound-guided percutaneous nephrolithotomy on renal calculus. Issue 24 (June 2017) - Fang, You-Qiang; Wu, Jie-Ying; Li, Teng-Cheng; Zheng, Hao-Feng; Liang, Guan-Can; Chen, Yan-Xiong; Hong, Xiao-Bin; Cai, Wei-Zhong; Zang, Zhi-Jun; Di, Jin-Ming
Abstract : Abstract: This study aimed to assess the role of pre-designed route on computer tomography urography (CTU) in the ultrasound-guided percutaneous nephrolithotomy (PCNL) for renal calculus. From August 2013 to May 2016, a total of 100 patients diagnosed with complex renal calculus in our hospital were randomly divided into CTU group and control group (without CTU assistance). CTU was used to design a rational route for puncturing in CTU group. Ultrasound was used in both groups to establish a working trace in the operation areas. Patients' perioperative parameters and postoperative complications were recorded. All operations were successfully performed, without transferring to open surgery. Time of channel establishment in CTU group (6.5 ± 4.3 minutes) was shorter than the control group (10.0 ± 6.7 minutes) ( P = .002). In addition, there was shorter operation time, lower rates of blood transfusion, secondary operation, and less establishing channels. The incidence of postoperative complications including residual stones, sepsis, severe hemorrhage, and perirenal hematoma was lower in CTU group than in control group. Pre-designing puncture route on CTU images would improve the puncturing accuracy, lessen establishing channels as well as improve the security in the ultrasound-guided PCNL for complex renal calculus, but at the cost of increased radiation exposure.